Perspectives from Singapore junior college students : what makes them good and smart? - Chia, Thien Huat Jae (2015)
In the 21st century, character education is regaining its importance. Some stud-ies have shown that academic excellence alone is insufficient for an individual to succeed. Character values such as resilience, determination, diligence are essential. On a macro level, character values such as empathy, integrity, respect are necessary for a gracious society. This research aims to answer the question of what platforms or programme in a school enables character development in the domains of ‘head’, ‘heart’ and ‘hands’. It seeks the answers from the per-spectives of the students of a Singapore junior college. The current and former students of the junior college were invited to complete an online questionnaire consisting of 36 statements with 5-point Likert scale where the participants answered how the character education through formal, hidden, and informal curricula had enabled them to develop their character. In the questionnaire, the participants were also given a descriptive question where they described a significant experience that had helped to develop their character. The key findings of the research were summarised as follows: firstly, for-mal curriculum is least impactful in all domains of character development. Sec-ondly, student-centred and social interaction experiences such as co-curricular activities, community involvement projects and academic group work have a significant impact on students’ adoption of character values and acting on them. Thirdly, co-curricular activities club is the single most impactful platform in character education although the kind of co-curricular activities does not matter.